Laryngeal neuroendocrine tumour: a case report on a rare pathology - Krishnan, Anand; Salaria, Neha; Singh, Anju; Mittal, Shubham (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2025)
Most of the laryngeal malignancies are squamous cell carcinomas. The neuroendocrine neoplasms (NENs) are rare tumours of larynx with high incidence of widespread metastases and poor prognosis. Here we are reporting an 87-year-old male with localised primary grade 3 neuroendocrine tumour with Ki67 positivity. He was treated with surgery followed by palliative radiotherapy and is on follow up. We report the rare case of laryngeal neuroendocrine tumour managed with direct laryngoscopic excision followed by radiotherapy.